Studies on Porous Nanostructured Palladium–Cobalt–Silica as Heterogeneous Catalysts for Oxygen Evolution Reaction - Prem. C. Pandey; Chitra Singh (My University, 2025)
Abstract: Co-NTA nanowires were used as a precursor in synthesizing Co@NC, CoPd@NC-1, and CoPd@NC-2 via active participation of 3-aminopropyltrimethoxysilane (3-APTMS). To regulate the existence of nanostructured silica after calcination at 700°C beneficial in OER, porous CoPd@NC was created using a variable amount of nanostructured silica in an N-doped carbon matrix. XRD, TEM, SEM, and EDX investigated coPd@NC-1 with high silica content and CoPd@NC-2 with relatively less silica content. Nanostructured silica enabled the formation of stabilized bimetallic Nano geometry of cobalt and palladium components, followed by improvement in OER compared to that made without nanostructured silica. The nanostructured silica-derived thin film made from CoPd@NC-1 generated a very high current density at a low potential of 0.79 V vs. RHE with current density of 10 mA cm–2 together small Tafel slope of 28 mV/decade for (CoPd@NC-1), 44 mV/decade for (CoPd@NC-2) at a catalyst loading of 3.5 mg cm–2 on the carbon cloth. © Pleiades Publishing, Ltd. 2024. ISSN 1023-1935, Russian Journal of Electrochemistry, 2024, Vol. 60, No. 9, pp. 749–759. Pleiades Publishing, Ltd., 2024.